Solubility of U(VI) in chloride solutions. I. The stable oxides/hydroxides in NaCl systems, solubility products, hydrolysis constants and SIT coefficients - Altmaier, Marcus; Fanghänel, Thomas (The journal of chemical thermodynamics, 2017)
The solubility of uranium(VI) is studied at T=(22±2)°C in carbonate-free 0.03-5.61mol·kgw−1 NaCl solutions at pHm=4-14.5 (pHm=−log [H+]). The solid phases metaschoepite UO3·2H2O(cr) and sodium uranate Na2U2O7·H2O(cr) (or NaUO2O(OH)(cr)) are characterized by XRD, SEM-EDS, thermogravimetry and quantitative chemical analysis. UO3·2H2O(cr) controls the solubility of U(VI) in acidic to near neutral pH conditions regardless of NaCl concentration. Na2U2O7·H2O(cr) forms in alkaline systems and is stable at pHm≥7 over the complete range of NaCl concentrations investigated. The solubility of UO3·2H2O(cr) at pHm<7 in NaCl solutions is very well described with the hydrolysis constants recommended by the NEA-TDB, a set of SIT coefficients evaluated in the present study and a solubility product of log*K°s,0{UO3·2H2O(cr)}=(5.35±0.13). Titration experiments and UV-vis absorption spectra of saturated solutions at pHm=4-5 in dilute to concentrated NaCl solutions confirm the speciation calculated in the present study and show the predominance of the trinuclear hydroxide complex (UO2)3(OH)42+ at high chloride concentrations. Solubility data obtained at 7≤pHm≤14.5 with Na2U2O7·H2O(cr) and in solutions equilibrated simultaneously with Na2U2O7·H2O(cr) and UO3·2H2O(cr) yield a solubility product of log*K°s,0{0.5 Na2U2O7·H2O(cr)}=(12.2±0.2) and the formation constants of the anionic hydrolysis species UO2(OH)3− (log*β°(1,3)=−(20.7±0.4)) and UO2(OH)42− (log*β°(1,4)=−(31.9±0.2)). SIT coefficients for these species are derived based on the solubility data obtained in dilute to concentrated NaCl systems. The chemical, thermodynamic and SIT activity models provided in this work for the system UVI-Na+-H+-Cl−-OH−-H2O(l) represent an accurate and robust tool for the calculation of U(VI) solubility and aqueous speciation in a variety of geochemical conditions relevant in the context of nuclear waste disposal.